Growth Mindset in Mathematics among Ninth-Grade Students via 5Ps Learning Model - Christian R Repuya (SEAMEO Regional Centre for QITEP in Mathematics, 2021)
This paper determined the effects of implementing the Prepare, Perform, Process, Ponder, and Practice (5Ps) learning model in teaching ninth-grade students’ growth mindset in mathematics. This study employed the quasi-experimental design and mixed-method research approach to answer the research questions with 60 ninth-grade students at a public secondary high school in the Philippines. The study administered a growth mindset questionnaire, informal interviews, learning journals, and Focus Group Discussions (FGD) on identifying learning experiences and mindsets of the students. Findings presented that employing the 5Ps learning model significantly influences students' mindset in mathematics. Meanwhile, traditional teaching does not significantly affect students' mindset in mathematics. The implementation of the 5Ps learning model has a significant positive effect on students' growth mindset in mathematics. The results of the study are limited merely to the participants included in the study; similar research utilizing the 5Ps learning model to other learning areas with a larger sample is recommended for more generalizable results.